Confirmed bacteriological diagnosis and cure of nonsevere gram-positive clinical mastitis cases enrolled in a randomized clinical trial based on results of on-farm culture - Q.K. Kolar; S.M. Godden; R.J. Erskine; P.L. Ruegg (JDS Communications)
Our objectives were to describe the confirmed bacteriological diagnosis of mastitis pathogens cultured from cases of nonsevere clinical mastitis (CM) identified as gram-positive (GP) using on-farm culture and to compare differences in bacteriological cure (BC) based on antimicrobial (AM) therapy. Cows that developed nonsevere CM in a single quarter were enrolled in a randomized clinical trial based on microbial growth on GP selective agars. Cows were randomly assigned to receive a once-daily intramammary treatment: 3 d hetacillin (n = 69), 3 d ceftiofur (n = 69), 8 d ceftiofur (n = 70), or to a nontreated group (n = 32). Etiologies were confirmed with MALDI-TOF using frozen duplicate milk samples. The crude proportion of BC was determined using milk samples collected at 14, 21, and 28 d after enrollment for cases caused by streptococci, NAS, Streptococcus-like organisms (consisting of Enterococcus and Lactococcus; SLO), and Staphylococcus aureus. Multivariable models were used to determine the effect of AM treatment on BC cure at d 21 for a subset of cases that had complete data for all covariates (n = 88). Growth on GP agar resulted in enrollment of 240 cases with confirmed etiologies distributed as Streptococcus spp. (21.7%; n = 52), Lactococcus spp. (19.2%; n = 46), NAS (16.3%; n = 39), Staph. aureus (6.3%; n = 16), Enterococcus spp. (5.0%; n = 12), and others (10%; n = 24). Thirty-five (14.5%) duplicate milk samples collected from enrolled cows had no significant growth in the laboratory and 16 (6.7%) were contaminated. Among sampling dates, combined crude BC for cases caused by target pathogens ranged from 68% to 71%. Crude BC ranged from 58% to 73% for the small group of nontreated cases (n = 12) and 69% to 71% for the combined group of cases that received intramammary AM (n = 113). Among all groups and all follow-up dates, crude BC was least for cases caused by Staph. aureus (ranging from 33% to 43%), followed by cases caused by SLO (58%–67%), NAS (79%–80%), and Streptococcus spp. (81%–91%). The proportion of BC at 21 d (LSM ± SE) did not vary between all cases that received AM (0.77 ± 0.06) and cases in the nontreated group (0.73 ± 0.16). The odds of BC at 21 d was about 5× greater for cases that occurred in primiparous as compared with multiparous cows and decreased 1.3-fold for each 1 log unit increase in SCC before the case. While this study does not have sufficient power to detect small differences in BC among pathogen groups or treatments, our results demonstrate that CM is caused by a wide diversity of GP bacteria with varying ranges of BC. These results provide justification for inclusion of negative control groups in future studies and confirm that important characteristics such as parity and history of subclinical mastitis influence the probability of BC.